HUBUNGAN SELF-ESTEEM DENGAN NOMOPHOBIA PADAMAHASISWA FAKULTAS KEDOKTERAN UNIVERSITASPEMBANGUNAN NASIONAL VETERAN JAKARTAANGKATAN 2019 - Neysa Ornella Dira (2020)
The high incidence of nomophobia in first-year medical students has become an important concern, especially during the COVID19's pandemic, which increases the need to use smartphones as a medium of learning and a source of information. The level of nomophobia in first-year students is influenced by how they value themself. Students with low self-esteem tend to have high levels of nomophobia. Short-term impacts include decrease in productivity and quality of life, while long-term ones the symptoms persist until students graduate and have an effect on performance in patient management. This study aims to determine the relationship between self-esteem and the level of nomophobia among medical students of the Universitas Pembangunan Nasional Veteran Jakarta class of 2019. This research uses an observational analysis with cross-sectional study approach using the Rosenberg Self-Esteem Scale and Nomophobia-Questionnaire which has been validated. Sampling of 44 respondents was done by consecutive sampling method. This study proves that there is a significant relationship between self-esteem and nomophobia (p = 0.001) in medical students of the Universitas Pembangunan Nasional Veteran Jakarta class of 2019.